Epigenetic cancer therapy - Gray, Steven G. (Amsterdam : Elsevier : Academic Press, 2015)
Epigenetic Cancer Therapy unites issues central to a translational audience actively seeking to understand the topic. It is ideal for cancer specialists, including oncologists and clinicians, but also provides valuable information for researchers, academics, students, governments, and decision-makers in the healthcare sector. The text covers the basic background of the epigenome, aberrant epigenetics, and its potential as a target for cancer therapy, and includes individual chapters on the state of epigenome knowledge in specific cancers (including lung, breast, prostate, liver). The bo.
4.3 Small-Molecule-Based miRNA Modulation5 Future Perspectives; Acknowledgments; References; 5 Long Noncoding RNAs and Cancer; 1 Introduction; 2 Classification and Nomenclature of lncRNAs; 2.1 Classification; 2.2 Nomenclature; 3 Mechanisms of lncRNA Function; 3.1 lncRNAs as Decoys and Guides; 3.2 lncRNAs as Scaffolds; 3.3 lncRNAs as Signaling Molecules; 3.4 miRNA Sequestration; 3.5 lncRNAs and Epigenetic Regulation; 3.5.1 H19; 3.5.2 AIR and KCNQ1OT1; 3.5.3 lincRNAs; 4 lncRNAs and Human Disease; 4.1 Prognostic Markers; 4.1.1 lncRNAs in the circulation
Includes index.
Academic Press is an imprint of Elsevier.
Includes bibliographical references at the end of each chapters and index.
Elsevier
Keywords: Cancer -- Gene therapy; Epigenetics; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Cancer -- Treatment; Cancer; Medicine; Cancer -- Gene therapy; Epigenetics; Electronic books; Electronic books